ANALISIS HUBUNGAN PENGGUNAAN KONTRASEPSI PADA WANITA DENGAN USIA MENOPAUSE - Lelly Aprilia Vidayati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Menopause is permanent cessation of menstruation after preceded by amenorhea for at least one year. Menopausal age in women can occur at age 45-50 years but in some circumstances can occur early or late. Age of menopause is influenced by several factors one them the use of hormonal contraception. The purpose of this study is to determine the relationship of contraceptive use in women with age of menopause in Polindes Tebul Kec. Kwanyar. This research use Analytical design with Cross Sectional approach. The independent variable is Contraception method and Dependent variable is age of menopause. The total population of 48 postmenopausal women from the study sample was 43 menopausal women. Sampling using simple random sampling technique. The instrument used is questionnaire. Univariate data analysis using frequency and bivariate distribution using chi square test with significant level α 0.05. The results showed that almost all menopausal women 43 people had a history of using hormonal contraception that is 24 people (55.8%). While 21 men (48.9%) of menopausal women had normal menopause, respondents who had a history of using hormonal contraceptives nearly half had normal menopause (48.9%). After chi square test with significant level α 0.05 obtained ρ Value: 0,008 <α: 0,05 so that H0 is rejected. This suggests that there is a relationship of contraceptive use in women with menopausal age. The conclusion of this study is that there is a relationship between contraceptive use in women with menopausal age, therefore it is advisable to menopause women to follow posyandu elderly to increase knowledge about menopause.